Determinants of health information verification: mediating roles of fake news awareness and network trust - Zaremohzzabieh, Zeinab; Ahmad Ghazali, Akmar Hayati; Ismail, Ismi Arif; Arshad, Mohd Mursyid; Mohd Zawawi, Julia Wirza (Penerbit Universiti Kebangsaan Malaysia, 2025)
In the digital era, the proliferation of health information necessitates individuals to evaluate its accuracy and reliability critically. This study investigates the influential factors in predicting health information verification behaviours, focusing particularly on trust in networks and fake news awareness as mediating variables. Data were collected from 400 social networking users across five Malaysian states and analysed using partial least squares structural equation modelling. The findings indicate that fake news awareness emerged as the most significant predictor of health information verification behaviour. Furthermore, social tie variety and information quality significantly predicted fake news awareness. Through the mediation of fake news awareness, indirect relationships between information quality, social tie variety, and health information verification behaviour were identified. These findings highlight the need for practical interventions, such as digital literacy programs and awareness campaigns, to enhance users' ability to critically assess health information. Such efforts are essential for empowering social media users to distinguish reliable information from misinformation, ultimately contributing to better public health outcomes. Going forward, this research deepens the understanding of health information verification behaviour, expands the health sector’s existing knowledge base, and provides a comprehensive framework that enriches our understanding of the factors influencing information verification behaviour within the context of health in a non-Western setting.